The seismotectonics of the Marmara region (Turkey): results from a microseismic experiment - Gurbuz, C; Aktar, M; Eyidogan, H; Cisternas, A; Haessler, H; Barka, A; Ergin, M; Turkelli, N; Polat, O; Ucer, SB; Kuleli, S; Baris, S; et al. (Elsevier BV, 2000)
The Marmara region is an active tectonic zone characterised by the transition between the dextral strike-slip regime of the North Anatolian Fault (NAF ) and the extension regime of the Aegean Sea. Strong historical earthquakes (M>7) and the presence of known seismic gaps imply a high level of seismic hazard. A synthesis of recent studies of active tectonics in the region is presented, including inland and underwater observations. The branching of the NAF is explained in terms of increasing influence of the extension. Historical information and instrumental seismicity are reinterpreted in order to have a critical appraisal of the existence of large seismic gaps in the central and eastern Marmara Sea. Focal mechanisms of strong earthquakes are used to obtain orientation and shape factor of the deviator of the stress tensor. The resulting tensor is in shear regime (s 2 vertical ) but close to extension (R=0.93) with s 1 oriented N145°0. A microseismic experiment with 48 stations distributed around the Marmara Sea was carried out in October‐December 1995. A total of 137 microearthquakes were located and 23 of those were selected to obtain focal mechanism solutions. The epicentral distribution indicates activity along the system of pull-apart basins north of the Marmara Sea. The segment between Marmara Sea and the Saros Bay, activated in 1912, and the Gulf of Izmit, site of the 1754 earthquake, are now silent. Seismic activity is very linear along the northern branch of the NAF, but it is more diVused on the Bursa and Iznik branches, southeast of the Marmara Sea. The stress tensor obtained from the focal mechanisms of the micro-earthquakes is compared to the one inverted from teleseismic data. The microseismic stress is compatible with a shear (intermediate) regime like the one obtained from strong earthquakes, though not as well constrained, one of the acceptable solutions having the same orientation but diVerent shape (R=0.5). © 2000 Elsevier Science B.V. All rights reserved.